Factors Associated With Transmission Of Nosocomial Infectious Diseases From Patients To Nurses At Rsu Royal Prima Medan - Halim, Michael; Ginting, Chrismis Novalinda; Chiuman, Linda (An-Nadaa: Jurnal Kesehatan Masyarakat (e-Journal), 2024)
Nosocomial infection is an infection acquired in the hospital for at least 72 hours, and the patient does not show symptoms of infection when admitted to the hospital. Nosocomial infections can have an impact on patients and their families which results in loss of sources of income, danger, disability, death, additional treatment periods, increased expenses for the hospital and can result in a lowered image of the hospital. The purpose of this study was to analyze the factors associated with the transmission of nosocomial infectious diseases from patients to nurses at RSU Royal Prima Medan. The type of research used is quantitative research with a cross sectional approach. The sample in this study were 200 nurses. Data analysis used univariate, bivariate and multivariate analysis. The results showed that partially there was a relationship between knowledge, attitudes, facilities, and cleanliness towards the transmission of nosocomial infectious diseases from patients to nurses at RSU Royal Prima Medan. Simultaneously or jointly the independent variables in this study are related to the transmission of nosocomial infectious diseases from patients to nurses at RSU Royal Prima Medan. The variable that is most related to the transmission of nosocomial infectious diseases from patients to nurses at RSU Royal Prima Medan is the attitude variable